2012
DOI: 10.1111/acps.12031
|View full text |Cite
|
Sign up to set email alerts
|

Differences in onset of disease and severity of psychopathology between toxoplasmosis‐related and toxoplasmosis‐unrelated schizophrenia

Abstract: Latent toxoplasmosis in schizophrenia may lead to more severe positive psychopathology and perhaps less favourable course of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
4
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 62 publications
1
45
4
5
Order By: Relevance
“…25 ). Finally, Toxoplasma seropositive schizophrenic patients have been shown to score significantly higher on the PANSS-positive subscale 26,27 and have reduced grey matter density compared with seronegative patients, 28 indicating that infection may be associated with exacerbated pathology. To our best knowledge, T gondii has not yet been detected in the brain of schizophrenia patients, but low infection levels often render it difficult to detect the parasite in tissues.…”
Section: Introductionmentioning
confidence: 99%
“…25 ). Finally, Toxoplasma seropositive schizophrenic patients have been shown to score significantly higher on the PANSS-positive subscale 26,27 and have reduced grey matter density compared with seronegative patients, 28 indicating that infection may be associated with exacerbated pathology. To our best knowledge, T gondii has not yet been detected in the brain of schizophrenia patients, but low infection levels often render it difficult to detect the parasite in tissues.…”
Section: Introductionmentioning
confidence: 99%
“…gondii infection has been associated with symptom severity in schizophrenia 23,27,28 . In addition, latent toxoplasmosis may have a negative impact on the disease course and treatment response in patients with schizophrenia 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical manifestations differ between seropositive and seronegative schizophrenic patients, with a predominance in the former of positive symptoms (delirium, hallucinations, disorganized thinking), cognitive disorders (abstract thinking difficulties, disorientation, attention deficit), and agitation [50,54]. Some researchers also observed that patients with schizophrenia and anti-T. gondii antibodies had a significantly higher risk of dying from natural causes [55] and were more likely to attempt suicide [56] in comparison with seronegative patients.…”
Section: Studies Based On the Detection Of Anti-toxoplasma Gondii Antmentioning
confidence: 99%